Orthodoxy, Orthopraxy, and Locke’s Arguments for Toleration - Ferg, Erica; Hall, Bryan (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2022)
A Letter Concerning Toleration (1689) comprises John Locke’s mature thoughts on religious toleration. In it, Locke offers three political arguments against state religious coercion. He argues that it is impossible, impermissible, and inadvisable for the civil magistrate to enforce ‘true religion,’ which Locke defines as the ‘inward and full persuasion of the mind’ (Works, 6:10). Notwithstanding the various internecine conflicts within Christianity, conflicts which motivated Locke’s concern with toleration, all of the many-splendored sects of Christianity nonetheless share the notion that orthodoxy (correct belief) is required for salvation. Since the early days of Christianity, orthodoxy has represented the lowest-common-denominator obligation of adherents to Christianity. Locke’s political arguments in the Letter, at least in their first instance, assume an orthodox definition of “true religion.” This is likewise true of those who have either defended or criticized Locke’s arguments in the secondary literature. In contrast to Locke and his commentators, we will argue that the dominant characterization of “true religion” globally and throughout history does not concern correct religious belief as much as it concerns correct religious practice, or orthopraxy. Even though it has not received as much attention in the literature, Locke does discuss orthopraxy–what he calls ‘outward worship’–at length in the second half of the Letter (Works, 6:29-39). We will demonstrate how versions of all three political arguments for toleration can be redeployed to constrain the power of the magistrate within an orthoprax conception of true religion.